Holocene hydrological and vegetation changes in southern France inferred by the study of an alluvial travertine system (Saint-Guilhem-le-Désert, Hérault) - Ali, Adam Ahmed; Roiron, Paul; Chabal, Lucie; Ambert, Paul; Gasco, Jean; André, Joël; Terral, Jean-Frédéric (Comptes Rendus Geoscience, 2008)
A geobotanical study of the travertine system of Saint-Guilhem-le-Désert (southern France) was carried out in order to reconstruct the local Holocene environment in a region where the postglacial vegetation history is poorly documented. The travertinisation process has started at ca. 8500 cal. BP, in a landscape dominated by Pinus sylvestris type (probably Pinus nigra sub sp. salzmannii). Around 7000 cal. BP, the travertine system recorded torrential events not evidenced at the regional scale, showing the particularity of the Verdus hydrological regime. More recently, ca. 5100 cal. BP, a lake or a marsh was ﬁlled within the Verdus plain, as attested to by sand and silt particles accumulated in the sequence. The present-day vegetation dominated by Quercus ilex, on south facing slopes, was most likely established between the Bronze Age and the Gallo-Roman period correlatively to the decline of Pinus nigra and deciduous Quercus, most probably under human inﬂuence
Keywords: 14C; Charcoals; Holocene; Leaf imprints; Southern France; Travertine; Vegetation dynamics

Holocene hydrological and vegetation changes in southern France inferred by the study of an alluvial travertine system (Saint-Guilhem-le-Désert, Hérault) - Ali, Adam Ahmed; Roiron, Paul; Chabal, Lucie; Ambert, Paul; Gasco, Jean; André, Joël; Terral, Jean-Frédéric (Comptes Rendus Geoscience, 2008)
A geobotanical study of the travertine system of Saint-Guilhem-le-Désert (southern France) was carried out in order to reconstruct the local Holocene environment in a region where the postglacial vegetation history is poorly documented. The travertinisation process has started at ca. 8500 cal. BP, in a landscape dominated by Pinus sylvestris type (probably Pinus nigra sub sp. salzmannii). Around 7000 cal. BP, the travertine system recorded torrential events not evidenced at the regional scale, showing the particularity of the Verdus hydrological regime. More recently, ca. 5100 cal. BP, a lake or a marsh was ﬁlled within the Verdus plain, as attested to by sand and silt particles accumulated in the sequence. The present-day vegetation dominated by Quercus ilex, on south facing slopes, was most likely established between the Bronze Age and the Gallo-Roman period correlatively to the decline of Pinus nigra and deciduous Quercus, most probably under human inﬂuence
Keywords: 14C; Charcoals; Holocene; Leaf imprints; Southern France; Travertine; Vegetation dynamics

Effects of fire frequency on plant communities and landscape pattern in the Massif des Aspres (southern France) - Trabaud, L; Galtié, J F (Landscape Ecology, 1996)
Fire frequency can affect pattern and diversity in plant communities and landscapes. We had the opportunity to study changes due to recurring wildfires on the same sites over a period of 50 years in the "Massif des Aspres" (southern France). The study was carried out in areas occupied by Quercus suber and Q. ilex series. A comparison of historical and cartographical documents (vegetation maps covering a 50 year interval and an accurate map of major wildfires during this period) allowed us to determine the changes occurring over time with or without fire action. Plant communities were grouped into three main vegetation types: forests, treed shrublands and shrublands. The passage of three successive wildfires on the same site led to a decrease in for- est areas and an increase in shrublands; however, shrublands were already present before the first fire of the period under consideration. Less frequent fire occurrence induced more complex heterogeneity and greater landscape diversity. In the study region as a whole, with or without fire action, a significant decrease in forest surfaces was recorded, whereas there was an increase of unforested communities such as treed shrublands and shrublands. In some parts of the Massif fires increased the homogeneity of the landscape, in other parts they created a greater heterogeneity and diversity of plant communities.
Keywords: aspres; fire; landscape diversity; Quercus ilex; Quercus suber; Southern France

Germination of Quercus ilex and Q. pubescens in a Q. ilex coppice - Bran, D; Lobreaux, O; Maistre, M; Perret, P; Romane, F (Plant Ecology, 1990)
Quercus ilex L. (holm oak) coppices, widespread around the Mediterranean basin, are probably the result of 5 000 years of prolonged human disturbance of the original Quercus pubescens Willd. (downy oak) forests. Since disturbance has almost ceased in recent years, a question arises as to the development of these coppices: will the Q. pubescens forests return, or will Q. ilex remain the dominant species? To investigate the phenomenon, we analyzed the first stages, i.e. germination of the two species in holm oak coppices. Our experiments show that both species germinated better in coppices than in clearings or clear-cuts. Moreover, Q. pubescens appears to be slightly favored above Q. ilex and it is suggested auto-allelopathy is involved, at least partially inhibiting the germination of Q. ilex.
Keywords: dynamics; Mediterranean climate; Southern France; succession

Local characterization of vegetation through growth forms: Mediterranean Quercus ilex coppice as an example - Floret, C; Galan, N J; Floc'h, E; Orshan, G; Romane, F (Plant Ecology, 1987)
Growth forms are considered from two viewpoints: a descriptive and a functional one. Mono-character growth forms and their biological spectra were used to test whether they can characterize certain underlying processes in Quercus ilex coppice in southern France. Correspondence analysis of 35 mono-character growth forms of 203 described taxa shows that location of renewal buds is a good integrating indicator of plant adaptations to the environment. Two of these characters (renewal bud location, Le. Raunkiaer's main life forms, and leaf consistency) appear to vary significantly along a gradient of increasing environmental constraints, especially climatic ones.
Keywords: coppice; growth form; Life form; Mediterranean climate; Quercus ilex L; Southern France

Inquadramento fitosociologico delle leccete dei dintorni di Siena - de Dominicis, Vincenzo (Giornale botanico italiano, 1973)
Abstract A phytosociological study of the Quercus ilex woods in the surroundings of Siena (Italy). Numerous stands of Quercus ilex woods around Siena have been studied phytosociologically and compared to the better known similar forests of Southern France. As a rule the Siennese Quercus ilex woods (Table 1) can not be considered to belong to the association Quercetum mediterraneo-montanum Br.-Bl. 1936 because of the absence of various significant central European and montane species, nor to Quercetum galloprovinciale because of the presence of too great a number of Quercetalia pubescenti-petraeae and Querco-Fagetea species. Only rarely communities similar to the first mentioned association have been found: i.e. on Mount Cetona at 1.800 feet and in two particularly cool and humid localities at a lower height (Table 2). Taking into account the way these woods have been managed for centuries it can be concluded that they are mixed formations of Quercetum galloprovinciale and an oakwood association belonging to the order Quercetalia pubescenti-petraeae; the exploitation techniques have caused the evergreen oak to become dominant therefore creating conditions favourable to the more thermophilous and shade loving plants characterics of Q. ilex woods and at the same time bringing about a sharp decrease in the number of the light demanding species typical of deciduous oakwoods.
Keywords: phytosociological study; Quercus ilex; Southern France